Replacement of Dietary Saturated by Unsaturated Fatty Acids: Effects on Platelet Protein Kinase C Activity, Urinary Content of 2,3-dinor-TXB2 and In Vitro Platelet Aggregation in Healthy Man - Turpeinen, Anu M.; Pajari, Anne-Maria; Freese, Riitta; Sauer, Roswitha; Mutanen, Marja (Thrombosis and Haemostasis, 1998)
The present study was conducted to compare the effects of oleic (OA) and linoleic acids (LA) on platelet function in healthy subjects. After a 4-week period on a diet rich in saturated fatty acids (SAFA), 38 volunteers (20 female, 18 male) had a high OA (18.0 en%) diet or a high LA diet (11.5 en%) for four weeks in a controlled manner. A control group of 13 subjects consumed their habitual diet throughout the study.Replacing the SAFA diet by the OA or LA diet did not affect the membrane-associated activity of platelet protein kinase C (PKC). However, both diets tended to increase the cytosolic activity to a comparable extent. Both the OA and the LA diets increased urinary excretion of 2,3-dinor-TXB2, as compared to the SAFA diet, whereas the urinary excretion of β-thromboglobulin remained unchanged. As compared to the initial SAFA diet, platelet aggregation to collagen increased after both diets, while ADP induced aggregation showed no diet-induced changes. The results indicate increased platelet activity after both oil diets with no differences between the OA and LA diet and confirm in vitro findings that cis-unsaturated fatty acids have a distinct effect on cytosolic PKC, in particular.